Efetividade e razão ótima de hedge para barril de petróleo - Vieira, Lucca Benchimol (Brasil, 2020)
Energy has a fundamental acting in the economic maintenance of each nation, and today, oil is the main sourcer considering the others, which turns it into a strategic and disputed asset, causing a good variation of its prices. Seeking to minimize the oscillatory risks of this troubled commodity that the practice of hedging is used. Therefore, the general objective of this study was to analyze the hedging operations of the oil barrel through the WTI futures contract, in order to obtain the optimal hedge ratio and its efficiency, for this purpose 26 models were generated for comparison. The results of the models with the best adjustment to reality showed an optimal hedge ratio (h) of 0.48 accompanied by an 84% risk mitigation effectiveness, whose value shows the importance of using the protective tool for oil traders.